Bài làm :
ĐKXD : \(x>0\) ; \(x\ne1\)
Rút gọn :
\(A=\left(\dfrac{1}{x-\sqrt{x}}+\dfrac{1}{\sqrt{x}-1}\right):\dfrac{\sqrt{x}+1}{\left(\sqrt{x}-1\right)^2}\)
\(A=\left(\dfrac{1}{x-\sqrt{x}}+\dfrac{\sqrt{x}}{x-\sqrt{x}}\right):\dfrac{\sqrt{x}+1}{\left(\sqrt{x}-1\right)^2}\)
\(A=\dfrac{1+\sqrt{x}}{x-\sqrt{x}}.\dfrac{\left(\sqrt{x}-1\right)^2}{\sqrt{x}+1}\)
\(A=\dfrac{\left(\sqrt{x}-1\right)^2}{\sqrt{x}\left(\sqrt{x}-1\right)}\)
\(A=\dfrac{\sqrt{x}-1}{\sqrt{x}}\)
Vậy \(A=\dfrac{\sqrt{x}-1}{\sqrt{x}}\)